2015
DOI: 10.3389/fncel.2015.00092
|View full text |Cite
|
Sign up to set email alerts
|

MCPH1: a window into brain development and evolution

Abstract: The development of the mammalian cerebral cortex involves a series of mechanisms: from patterning, progenitor cell proliferation and differentiation, to neuronal migration. Many factors influence the development of the cerebral cortex to its normal size and neuronal composition. Of these, the mechanisms that influence the proliferation and differentiation of neural progenitor cells are of particular interest, as they may have the greatest consequence on brain size, not only during development but also in evolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 157 publications
0
55
0
Order By: Relevance
“…Experiments on chicken cells using various truncated forms of chicken Mcph1 showed that BRCT1 is necessary for centrosomal localization, whereas BRCT2 and BRCT3 are required for IRIF formation and response to DNA damage (Pulvers et al., ). The study of the two major transcripts of MCPH1 (full‐length MCPH1, and a transcript lacking exons 9 to 14) also showed that the C‐terminus of the protein was necessary for DNA damage response.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments on chicken cells using various truncated forms of chicken Mcph1 showed that BRCT1 is necessary for centrosomal localization, whereas BRCT2 and BRCT3 are required for IRIF formation and response to DNA damage (Pulvers et al., ). The study of the two major transcripts of MCPH1 (full‐length MCPH1, and a transcript lacking exons 9 to 14) also showed that the C‐terminus of the protein was necessary for DNA damage response.…”
Section: Discussionmentioning
confidence: 99%
“…The mouse ortholog of MCPH1, containing 822 aa, has 57% homology to the human protein [6]. Several Mcph1-knockout mouse models have been generated [44]. The first…”
Section: Mcph1 and Brain Development: Lessons From Mouse Modelsmentioning
confidence: 99%
“…The brain size is primarily dependent on the capacity of neuroprogenitor proliferation and self-renewal [43,44].…”
Section: Mcph1 and Brain Development: Lessons From Mouse Modelsmentioning
confidence: 99%
“…Some evidence suggests that the human brain is still adaptively evolving [1], and that positive selection may also play an essential role in the development of speech [2], and in the enabling of adults to digest the lactose contained in milk [3][4][5][6]. Moreover, understanding how and why selection acts can help us to reveal the mechanisms that underlie diseases and microbial resistance [7].…”
Section: Introductionmentioning
confidence: 99%
“…This increasing interest can be seen in the increasing number of citations of three key methodological papers [8][9][10] (Figure 1). 1 demography could be one of the major reasons for 86% of the unique candidates. This has consequences.…”
Section: Introductionmentioning
confidence: 99%